The draft genome sequence of the nematode Caenorhabditis briggsae, a companion to C. elegans - Gupta, Bhagwati P (BioMed Central, 2003)
The publication of the draft genome sequence of Caenorhabditis briggsae improves the annotation of the genome of its close relative Caenorhabditis elegans and will facilitate comparative genomics and the study of the evolutionary changes during development.